Photodynamic Therapy in the Inactivation of Microorganisms - Adelaide Almeida (MDPI AG, 2020)
The growing emergence of microbial resistance to conventional antimicrobials, due their dissemination in the environment, and excessive or inadequate prescriptions, associated with the globalization of pathogenic microorganisms’ transmission, make the discovery of new effective therapies to combat infection of extreme urgency [...]